The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1080/02786820300913
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of an Improved Particle Size Magnifier (PSM) for Single Nanoparticle Detection

Abstract: Several modifications of the particle size magnifier (PSM) developed by Okuyama et al. have been introduced recently for detection of particles at diameters of 1 nm and below. However, their evaluation has been incomplete. Here we provide the first direct measurements of counting efficiencies near unity below 2 nm. We use the modified PSM described by Sgro and Fernández de la Mora, which separates thermally the PSM's original vapor generator from the water-cooled growth chamber by means of a narrow and short T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…Kim et al (2003) showed that the diameter of grown droplets at the exit of an ethylene glycol based mixing type CPC could be all detected by a laser particle counter with a minimum detection size of 0.1 μm; therefore, our calculated results are qualitatively consistent with their experimental observations. While particles in the 1 μm diameter range can be detected by light scattering, they would be more difficult to detect than the 10 μm droplets produced by butanol instruments.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Kim et al (2003) showed that the diameter of grown droplets at the exit of an ethylene glycol based mixing type CPC could be all detected by a laser particle counter with a minimum detection size of 0.1 μm; therefore, our calculated results are qualitatively consistent with their experimental observations. While particles in the 1 μm diameter range can be detected by light scattering, they would be more difficult to detect than the 10 μm droplets produced by butanol instruments.…”
Section: Resultssupporting
confidence: 82%
“…First, negatively charged particles are more easily activated than positively charged particles. The polarity dependence of the activation efficiency of charged particles has been observed in previous experimental studies using an ethylene glycol based mixing type CPC (Kim et al 2003) and a propanol based expansion type CPC (Winkler et al 2006b(Winkler et al , 2008. The activated fractions at given sizes using oleic acid are generally lower than those obtained using diethylene glycol.…”
Section: Activation Efficiencymentioning
confidence: 78%
See 1 more Smart Citation
“…He used diethylene glygol or oleic acid vapor to activate the particles and magnify their size so that they were detectable with an ordinary butanol CPC. Very low cut-sizes are reported also for mixing type CPCs (Okuyama et al 1984;Seto et al 1997; Gamero-Gastaño and Fernández de la Mora 2002; Kim et al 2003;Sgro and Fernández de la Mora 2004). For example the mixing type CPC-or "particle size magnifier"-of Seto et al (1997) was able to activate and grow singly charged ions down to approximately 1 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…A recent progress in the field of atmospheric aerosol science, especially in understanding of the new particle formation (Kulmala et al 2004), as well as the bloom of nanoscience and -technology have created a need to develop CPCs for detection of smaller and smaller particles. Mixing type particle size magnifiers (PSM) developed by Gamero-Castaño and Fernandez de la Mora (2000), Kim et al (2000), and Sgro and Fernández de la Mora (2004) has shown a superior performance in the sub-3nm size range. However, no reports on their applicability in, e.g., atmospheric studies exist.…”
Section: Introductionmentioning
confidence: 99%